FAM19A5 Expression During Embryogenesis and in the Adult Traumatic Brain of FAM19A5-LacZ Knock-in Mice - Shahapal, Anu; Cho, Eun Bee; Yong, Hyo Jeong; Jeong, Inyoung; Kwak, Hoyun; Lee, Jae Keun; Kim, Wonkyum; Kim, Bongcheol; Park, Hae-Chul; Lee, Won Suk; Kim, Hyun; Hwang, Jong-Ik; et al. (Frontiers in Neuroscience, 2019)
FAM19A5 is a secretory protein that is predominantly expressed in the brain. Although the FAM19A5 gene has been found to be associated with neurological and/or psychiatric diseases, only limited information is available on its function in the brain. Using FAM19A5-LacZ knock-in mice, we determined the expression pattern of FAM19A5 in developing and adult brains and identified cell types that express FAM19A5 in naïve and traumatic brain injury (TBI)–induced brains. According to X-gal staining results, FAM19A5 is expressed in the ventricular zone and ganglionic eminence at a very early stage of brain development, suggesting its functions are related to the generation of neural stem cells and oligodendrocyte precursor cells (OPCs). In the later stages of developing embryos and in adult mice, FAM19A5 expression expanded broadly to particular regions of the brain, including layers 2/3 and 5 of the cortex, cornu amonis (CA) region of the hippocampus, and the corpus callosum. X-gal staining combined with immunostaining for a variety of cell-type markers revealed that FAM19A5 is expressed in many different cell types, including neurons, OPCs, astrocytes, and microglia; however, only some populations of these cell types produce FAM19A5. In a subpopulation of neuronal cells, TBI led to increased X-gal staining that extended to the nucleus, marked by slightly condensed content and increased heterochromatin formation along the nuclear border. Similarly, nuclear extension of X-gal staining occurred in a subpopulation of OPCs in the corpus callosum of the TBI-induced brain. Together, these results suggest that FAM19A5 plays a role in nervous system development from an early stage and increases its expression in response to pathological conditions in subsets of neurons and OPCs of the adult brain.